Utility of a Point-of-Care Malaria Rapid Diagnostic Test for Excluding Malaria as the Cause of Fever among HIV-Positive Adults in Rural Rakai, Uganda - Mills, Lisa A. (The American Society of Tropical Medicine and Hygiene, 2010)
We compared results of a malaria rapid diagnostic test (Binax Now(®) Malaria, Binax-M, Inverness Medical Innovations, Inc., Waltham, MA) performed at rural mobile clinics in Uganda by clinicians evaluating febrile adult HIV patients to thick smear evaluated at a central laboratory by trained microscopists. Two hundred forty-six samples were analyzed, including 14 (5.7%) which were thick-smear positive for falciparum malaria. Sensitivity of Binax-M compared with thick smear was 85.7% (95% CI: 57.2–98.2), specificity 97.8% (95% CI: 94.9–99.3), positive and negative predictive values were 70.6% (95% CI: 44.0–89.7) and 99.1% (95% CI: 96.8–99.9), respectively. The rapid diagnostic test accurately ruled malaria “in or out” at the point-of-care, facilitating appropriate clinical management and averting unnecessary anti-malarial therapy.